Differences In The Inheritance Rights of Men And Women In Islamic Law (Psychological Studies) - Sammak, Jusalim; Iftitah, Nurimah (CV Media Inti Teknologi, 2025)
Background of the study: Islamic inheritance law assigns a male heir twice the share of a female under certain conditions. This provision often raises debates on gender justice, especially from a modern and psychological standpoint, where emotional perceptions of fairness are questioned.Purpose and scope of the paper: This study aims to examine public perceptions of the gender-based differences in Islamic inheritance distribution and explore the psychological impact, particularly on female heirs. The study combines normative analysis with empirical insights from Muslim communities involved in inheritance cases.Methods: A qualitative approach was used, involving in-depth interviews, participant observation, and document analysis. Data were analyzed thematically using a social psychology framework to understand the emotional, cognitive, and value-driven responses related to inheritance practices.Results: The findings indicate that while Islamic inheritance law is rooted in the principle of social responsibility, some women experience emotional injustice, especially those with significant economic contributions. This perception is closely linked to limited understanding of maqāṣid al-syarī‘ah and the broader social context of Islamic law.Conclusion: The study emphasizes the need for integrative Islamic legal education that includes psychological and contextual dimensions. In the long term, this research contributes to building more humanistic interpretations of Islamic law and informs future development of educational, policy, and counseling strategies to support fairer and more spiritually accepted inheritance practices.